MENGKAJI PERAN MASJID ANNUQOBAH BAGI MASYARAKAT KOTA PRABUMULIH - Zahirah, Aliyah; Hidayah, Arina Asmal; Savitr, Mutiara Raya; Selamata, Viora; Hudaidah (BANDA HISTORIA: Jurnal Pendidikan Sejarah dan Studi Budaya, 2025)
The mosque is a place of worship for Muslims to perform prayers, pray, recite the Koran and various other worship services. The mosque is also referred to as Baitullah (the house of Allah). This article describes how the Annuqobah mosque plays a role for the communityin the city of Prabumulih. Qualitative methods are used in this research by collecting data sources from interviews with community leaders, mosque administrators, and worshipers. The results show that the Annuqobah Mosque contributes greatly to fostering a sense of solidarity and togetherness among residents, which helps strengthen the community's social network, the mosque also plays an important role in religious education and character development of the younger generation. This research has high significance because it can add to the treasure of literature on the role of mosques in Indonesia that has not been found in previous studies and provide guidelines for policy makers, community leaders, and social organizations in order to create more efficient programs to empower communities through the use of mosques as activity centers. The conclusion shows that the Annuqobah mosque plays a role in shaping community identity and strengthening religious values. Therefore, to strengthen its role in the future, it is necessary to increase community support and participation in mosque activities.